Secondhand tobacco smoke exposure and pulmonary function: a cross-sectional study among non-smoking employees of bar and restaurants in Santiago, Chile - Parro, Javiera (BMJ Open, 2017)
INTRODUCTION: The workplace remains a significant source of secondhand smoke (SHS) exposure. This pollutant is known to be associated with respiratory and cardiovascular problems, but its effects on specific pulmonary function parameters remain largely unexplored. The objectives of this study were to measure SHS exposure among non-smoking employees of bar and restaurants in Santiago, Chile and to evaluate the effects of such exposure on pulmonary function. METHODS: Cross-sectional design. The study sample included non-smoking workers from 57 restaurants and bars in Santiago, Chile. The outcome variable was pulmonary function and the exposure variables were urine cotinine concentration, a biomarker for current SHS exposure, and years of SHS exposure in the workplace as proxy of chronic exposure. Personal and occupational variables were also recorded. Data analysis was performed using linear regression models adjusted by confounders. RESULTS: The median age of the workers was 35 years and the median employment duration at the analysed venues was 1 year. Workers in smoking facilities reported greater SHS exposure (36 hours per week) than workers in smoke-free locations (4 hours per week). Urine cotinine levels were inversely correlated with forced vital capacity, but the finding was not statistically significant (β=−0.0002; 95% CI −0.007 to 0.006). Years of exposure to SHS showed to be significantly associated with forced expiratory flow(25/75) (β=−0.006; 95% CI −0.010 to −0.0004). CONCLUSION: These findings suggest that cumulative exposure to SHS at work may contribute to deterioration of pulmonary function in non-smoking employees.